Viologen-derived material showing photochromic, visually oxygen responsive, and photomodulated luminescence behaviors. Issue 4 (5th January 2021) - Li, Zhao-Hao; Xue, Li-Ping; Mu, Yun-Jing; Zhao, Bang-Tun
Abstract : A new 2D viologen-derived Zn(ii ) photochromic material exhibits photochromic, visually oxygen responsive, and photomodulated luminescent behaviors. Abstract : The synthesis of photochromic functional materials with excellent performances is important owing to their workable applications. In this study, a new viologen-derived Zn(ii ) material with a two-dimensional layered structure, namely {[Zn(L)(cpbpy)](H2 O)3 } n (1 ; H2 L = 2, 5-thiophenedicarboxylic acid; cpbpy = N -(3-carboxypyridin-5-yl)-4, 4′-bipyridinium), was fabricated based on a new mono-substituted viologen derivative via a solvothermal synthesis. Similar to materials containing viologens, 1 displayed a photochromic behavior upon xenon light irradiation. Interestingly, its dehydrated product 1a exhibited a rapid photochromism only under vacuum or an inert atmosphere, which makes 1a a potential O2 sensitive material. Further investigations show that 1 and 1a had remarkably different photomodulated luminescence behaviors. This study widens the application of such a viologen derivative towards constructing new photochromic materials having a rapid photochromic response.